PP.13.12: DELETION OF THE MAS RECEPTOR AGGRAVATES THE DEVELOPMENT OF ATHEROSCLEROSIS AND ABDOMINAL AORTIC ANEURYSMS IN APOLIPOPROTEIN E-DEFICIENT MICE. (June 2015) - Yang, G.; Grave, K.; Thieme, M.; Hoch, H.; Hering, L.; Rump, L.C.; Stegbauer, J.
Abstract : Objective: Atherosclerosis and hypertension are commonly observed in patients and strongly associated with increased mortality. Recently, we have shown that chronic Ang-(1–7) treatment acting through the Mas receptor improves vascular dysfunction in atherosclerotic apolipoprotein E-deficient (apoE-/-) mice. To test whether the G-protein-coupled Mas receptors plays also role in the development of atherosclerosis and abdominal aortic aneurysm (AAA), we generated apoE/Mas receptor deficient (apoE-/-/Mas-/-). Design and method: ApoE-/- and apoE-/-/Mas-/- mice fed on a lipid-rich Western diet were treated via osmotic minipumps with either saline or Ang-(1–7) (82 μgkg(-1) h(-1)) for 6 weeks. Aortae were stained with red oil and quantified for atherosclerosis. To better recognize the meaning of Mas receptors in the formation of AAA, both mice were infused with angiotensin II (AngII) (1000 ng/kg/min) for 4 weeks. Maximal external abdominal aortic diameter was measured by ultrasound in vivo and ex vivo on formalin fixed tissues. Results: Atherosclerosis was significantly increased in apoE-/-/Mas-/- mice compared to apoE-/- (relative lesion area of the aortic arch: 38.7 ± 3.0 vs. 25.4 ± 2.0%; P < 0.01; specific lesion area 11.7 ± 0.9 vs. 8.1 ± 1.0 mm 2 P < 0.01). In contrast, chronic Ang-(1–7) infusion significantly attenuates atherosclerotic leasions in apoe-/- (apoE-/-/ vs. apoE-/- + Ang-(1–7): 25.4 ± 2.0 vs. 11.1 ± 2.6% P < 0.01 and 8.1 ± 1.0 vs. 3.1 ± 0.8 mm 2 P < 0.01) but not in apoE-/-/Mas-/- mice (apoE-/-/Mas-/- vs. apoE-/-/Mas-/ + Ang-(1–7): 38.7 ± 3.0 vs. 38.0 ± 14.2% and 11.7 ± 0.9 vs. 11.4 ± 5.0 mm 2 ). During chronic Ang II infusion, the incidence of AAA was increased in apoE-/-/Mas-/- compared to the apoE-/- mice (75% vs. 45% n = 8–11). Moreover, the maximal external abdominal aortic diameter was significantly larger in Ang II treated apoE-/-/Mas-/- mice compared to Ang II treated apoE-/- mice (2.24 ± 0.22 mm vs. 1.51 ± 0.17 mm; P < 0.05). Interestingly, blood pressures and cardiac hypertrophy did not differ during chronic AngII infusions in apoE-/- and apoE-/-/Mas-/- mice suggesting that the incidence and the extend of AAA seemed to be blood pressure independent. Conclusions: These findings indicate an important role for the Mas receptors in the progress of atherosclerosis and AAAs. Chronic Ang-(1–7) infusion stimulates the Mas receptor and attenuates atherosclerosis. Further research is required to investigate the underlying mechanisms and the specific cell type responsible for these findings.